2020
DOI: 10.3390/pathogens9110867
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Infection of Bat Pipistrellus nathusii Epithelial cells Depends on the Invasion Factors InlA and InlB

Abstract: L. monocytogenes is a widespread facultative intracellular pathogen. The range of natural hosts that supporting L. monocytogenes persistence in the environment has not been fully established yet. In this study, we were interested in the potential of L. monocytogenes to infect cells of bats, which are being increasingly recognized as a reservoir for microorganisms that are pathogenic to humans and domestic animals. A stable epithelial cell line was developed from the kidneys of Pipistrellus nathusii, a small ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…To visualize the death of neighboring host cells, we applied a standard macroscopic plaque assay using neutral red solution staining ( Sun et al, 1990 ). Nevertheless, although this approach worked well in different cell models, including mouse L2 cell fibroblasts, human intestinal HT-29 cells, and bat kidney epithelial cells ( Sun et al, 1990 ; Roche et al, 2001 ; Povolyaeva et al, 2020 ), the standard assay did not reveal visible plaques in the shKEC monolayer even after 10 days of incubation (data not shown). To resolve the question of whether L. monocytogenes could move from cell to cell, we studied infected shKEC monolayers by using light microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To visualize the death of neighboring host cells, we applied a standard macroscopic plaque assay using neutral red solution staining ( Sun et al, 1990 ). Nevertheless, although this approach worked well in different cell models, including mouse L2 cell fibroblasts, human intestinal HT-29 cells, and bat kidney epithelial cells ( Sun et al, 1990 ; Roche et al, 2001 ; Povolyaeva et al, 2020 ), the standard assay did not reveal visible plaques in the shKEC monolayer even after 10 days of incubation (data not shown). To resolve the question of whether L. monocytogenes could move from cell to cell, we studied infected shKEC monolayers by using light microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…InlB is one of major invasion factors that provides L. monocytogenes invasion into epithelial cells via interactions with its target receptor c-Met ( Bierne and Cossart, 2002 ). InlB was shown to provide species-specific interactions of L. monocytogenes with the guinea pig, rabbit, and bat cells ( Khelef et al, 2006 ; Povolyaeva et al, 2020 ). The diagram of the structure of c-Met with the indication of the main domains is shown ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, our group developed a stable epithelial cell line from the kidneys of P. nathusii (PKDCL) [9]. In another study, this diploid cell line demonstrated the ability to maintain reproductions of Bluetongue virus, Rift Valley fever, Lumpy skin disease virus and Myxoma virus [10].…”
Section: Introductionmentioning
confidence: 99%